The intensity or duration of inflammatory back pain has no impact on the detection of sacroiliitis by magnetic resonance imaging in axial spondyloarthritis - BIYIKLI, ERHAN; BUĞDAYCI, ONUR; KUTLUĞ AĞAÇKIRAN, SEDA; ATAGÜNDÜZ, MEHMET PAMİR (My University, 2023)
Background: Sacroiliac joint (SIJ) magnetic resonance imaging (MRI) is an established tool in the evaluation of patients with axial spondyloarthritis (axSpA). In the validation study of the ASAS classification criteria for axSpA, only 63.1% of patients had sacroiliitis on the SIJ-MRI.[1] Studies that enrolled patients with axSpA based on expert opinion reported the sensitivity of MRI between 35 to 42% in detecting sacroiliitis.[2,3] Objectives: This study aimed to evaluate the temporal relationship between ASAS defined positive MRI and the characteristics of low back pain (LBP) in axSpA. Methods: Following axSpA groups were enrolled in the study whenever an attending physician ordered an SIJ-MRI. Patients fulfilling both the Rudwaleit criteria for inflammatory back pain (IBP) and Amor criteria, patients with a previous classification with either modified New York or ASAS classification criteria.[1] A blinded rheumatologist (GS) recorded the intensity and duration of IBP using a questionnaire before SIJ-MRI. MRI appointments were based on availability. Therefore some patients did not have IBP at acquisition. Two radiologists assessed SIJ-MRIs using the ASAS/OMERACT MRI group definition of active sacroiliitis.[4] In case of discrepant reporting, a third experienced radiologist (GE) adjudicated the SIJ-MRIs. The probability of axSpA is estimated using sum scores for SpA features excluding the SIJ-MRI.[5] The correlation between an ASAS-defined positive MRI and LBP characteristics was analyzed. Results: Fifty-nine patients (32 F/27M) were included. Patient characteristics are given in Table 1. Overall, 28 of 59 patients (47.5%) had a positive SIJ-MRI defined by ASAS. The median duration of LBP was 15 (43) days and the highest intensity of LBP was felt 6.5 ± 1.2 days before the MRI appointment. At acqusition, 13 (22.0%) patients reported no LBP. There was no significant difference between the presence of LBP within 10 days prior to MRI and sacroiliitis on MRI. (p=0.6) (Sacroiliitis in 45.7% with, and 53.8% without LBP) In LBP reporting patients, pain duration and pain VAS score were 3.3 ±2.3 and 7.1 ±1.9 in patients with sacroiliitis, and 8.7 ±3.6 and 6.8 ±1.7 in patients without sacroiliitis on MRI, respectively. (p=0.48, p=0.10) Age, sex, BASDAI, CRP and calculated probability of axSpA had no correlation with the presence of sacroiliitis on MRI. Adding sacroiliitis on SIJ-MRI to axSpA probability score increased the rate of patients with a probability of >90% for axSpA from 71.2 to 83.1% but the rate of sacroiliitis on MRI was similar in all probability groups. Conclusion: These results suggest that the presence of LBP and the duration of intense pain do not affect the detected rate of sacroiliitis on SIJ-MRI in axSPA. The low prevalence of sacroiliitis in this study population implies its value as a classification tool. Further studies with larger sample sizes are needed to clarify the factors affecting the SIJ-MRI findings in axSpA patients.